Occupational exposure to blood-borne pathogens among health workers at a tertiary hospital in China during 2016–2022: multi-round evaluation of comprehensive intervention - Shen, Wenya; Zhang, Min; He, Chuning; Huang, Yiming; Fang, Xinxin; Wu, Jing; Tang, Yuting; Wang, Li (Frontiers in Public Health, 2025)
ObjectiveOccupational blood-borne pathogens exposure (OBPE) exist in all healthcare settings, and pose potential risk to health workers (HWs), comprehensive interventions are the key. This study aimed to evaluate the prevention and control measures at a tertiary hospital with 2025 beds in southern China.MethodsWith the intervention of the national and international technical tools/guidance, two cross-sectional surveys were conducted in 2016 (pre-) and 2022 (post-) with the same questionnaire and methodology, respectively.ResultsThe incidence rate of OBPE was significantly decreased from 14.98% (2016) to 4.94% (2022) with HWs 1052 (2016) and 3080 (2022), respectively. The average number of episodes in OBPE decreased from 0.19 (2016) to 0.07 (2022) per person per year. The OBPE knowledge training rate for HWs has significantly improved with an increase by 24.30% (pre-employment) and 9.85% (on-the-job). The reporting rate of OBPE was significantly increased from 29.97% (2016) to 63.96% (2022). However, hepatitis B vaccination coverage decreased from 80.15% (2016) to 71.71% (2022), level of awareness in HBsAb status decreased from 71.32% (2016) to 58.05% (2022), HBsAb positive rate decreased from 54.80% (2016) to 39.70% (2022). The reporting rates for OBPE rose from 28.97% (2016) to 63.96% (2022), The OBPE reporting rate increased by 1.21 times. Besides, influencing factors of OBPE indicated that department, vaccination, HBsAb status, knowledge scores, working time, HBV infection status and whether report occupational health issues to the hospital were related to the occurrence of OBPE.ConclusionOccupational health for all HWs should not be achieved once and for all, it requires a sustainable investment by systematic interventions. The valuable experiences and lessons derived here can be shared beyond the hospital in China and globally.